2021
DOI: 10.3991/ijet.v16i07.21175
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Student’s Soft-Skill by Web-Based EColloquium Learning Approach to Enhance Advance Feedbacks

Abstract: The use of information technology in learning has become a demand for the implementation of modern education. Various patterns of technology integration in learning are proposed to improve optimal learning outcomes. This study aims to develop learning media in the form of web-based e-colloquium to increase students’ soft-skills. This development used research and development method with the ADDIE model (analyzing, designing, developing, implementing, and evaluating). This study found that web-based E-colloquiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Cost related to the acquisition of digital teaching solutions such as games and specific software (Scherer, Siddiq & Tondeur, 2019) and the dependence on practical activities (Kaarakainen & Saikkonen, 2021) influences how easy the pedagogical approach can be converted in distance learning. Regular e-learning tools can have a wide array of possibilities, from digital textbooks (Lau et al, 2018), to highly interactive activities such as Web-based learning (WBL) (Adi, Kurniawan & Siddik, 2021) and the uses of machine learning-based platforms (Balica, 2018). Therefore it is possible to work on a gradient between the complexity of tool resources and interaction demands, and the gradient is empowered by the perspective of the digital readiness of the millennial generation.…”
Section: Socioemotional Skills For Ti In the Covid-19 Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Cost related to the acquisition of digital teaching solutions such as games and specific software (Scherer, Siddiq & Tondeur, 2019) and the dependence on practical activities (Kaarakainen & Saikkonen, 2021) influences how easy the pedagogical approach can be converted in distance learning. Regular e-learning tools can have a wide array of possibilities, from digital textbooks (Lau et al, 2018), to highly interactive activities such as Web-based learning (WBL) (Adi, Kurniawan & Siddik, 2021) and the uses of machine learning-based platforms (Balica, 2018). Therefore it is possible to work on a gradient between the complexity of tool resources and interaction demands, and the gradient is empowered by the perspective of the digital readiness of the millennial generation.…”
Section: Socioemotional Skills For Ti In the Covid-19 Eramentioning
confidence: 99%
“…To achieve a long-lasting and meaningful education, the process must be grounded on discursive, interactive, and reflexivity activities, and this is both a call and also a shortcoming of digital e-learning solutions (Laurillard, 2002). Studies show that digital education can act in both ways, also being successful in fostering the development of general communication skills and mental readiness (Adi, Kurniawan & Siddik, 2021).…”
Section: Socioemotional Skills For Ti In the Covid-19 Eramentioning
confidence: 99%
“…Especially students who take courses to be able to use it as part of the process of disseminating suggestions they have made, and receiving feedback from various parties to improve the suggestions that have been made. For example, based on the results of the expert assessment and the feedback from students, which were processed and analyzed based on common tools, the researchers concluded that the electronic platform should be used and used as a teaching aid (Idris et al, 2021). In addition, electronic platforms and resources can be effectively used as tools for harmonization and management of the acquisition of competencies by students of higher education (Idrees et al, 2021).…”
Section: педагогIка сів які є корисними при їх проєктуванні інтелекту...mentioning
confidence: 99%
“…Especially students who take courses to be able to use it as part of the process of disseminating suggestions they have made, and receiving feedback from various parties to improve the suggestions that have been made. For example, based on the results of the expert assessment and the feedback from students, which were processed and analyzed based on common tools, the researchers concluded that the electronic platform should be used and used as a teaching aid (Idris et al, 2021). In addition, electronic platforms and resources can be effectively used as tools for harmonization and management of the acquisition of competencies by students of higher education (Idrees et al, 2021).…”
Section: гармонізація та управління знаннями студентів за використанн...mentioning
confidence: 99%